Fungal Microbiota Dysbiosis and Ecological Alterations in Gastric Cancer - Yang, Ping; Zhang, Xiaoshan; Xu, Rui; Adeel, Khan; Lu, Xiaofeng; Chen, Min; Shen, Han; Li, Zhiyang; Xu, Zhipeng (Frontiers in Microbiology, 2022)
Changes in bacteriome composition have a strong association with gastric cancer (GC). However, the relationship between stomach fungal microbiota composition and human host immune factors remains largely unknown. With high-throughput internal transcribed spacer region 2 (ITS2) sequencing, we characterized gastric fungal microbiome among the GC (n = 22), matched para-GC (n = 22), and healthy individuals (n = 11). A total of 4.5 million valid tags were generated and stratified into 1,631 operational taxonomic units (OTUs), and 10 phyla and 301 genera were identified. The presence of GC was associated with a distinct gastric fungal mycobiome signature, characterized by a decreased biodiversity and richness and significant differences in fungal composition. In addition, fungal dysbiosis was reflected by the increased ratio of Basidiomycota to Ascomycota and a higher proportion of opportunistic fungi, such as Cutaneotrichosporon and Malassezia, as well as the loss of Rhizopus and Rhodotorula during the progression of cancers. A panel of GC-associated fungi (e.g., Cutaneotrichosporon and Rhodotorula) was found to adequately exhibit diagnostic value. Furthermore, the mRNA levels of cytokines and chemokines were detected and correlated with the specific fungal dysbiosis, indicating the possible mechanism of GC. This study reveals GC-associated mycobiome dysbiosis characterized by altered fungal composition and ecology and suggests that the fungal mycobiome might play a role in the pathogenesis of GC.